Características físico-químicas e compostos bioativos de frutos de oliveira ao longo do desenvolvimento - Laura Ciribelli Borges (2016)
The olive tree, temperate plant from oleaceae family, has been grown in several countries, including Brazil. Studies characterizing the cultivars adapted to this country as Arbequina and Grappolo 541 may contribute to the production of olive products of high quality. The objective of this study was to investigate the physicochemical characteristics and bioactive compounds in Arbequina and Grappolo 541 olives cultivated in Maria da Fé, MG, Brazil, harvested at 86, 106, 124, 141, 162 and 177 days after anthesis or bloom. Physical dimensions (longitudinal and transversal diameters, mass and pulp-stone ratio - PSR) and contents of total lipids, moisture, total phenolics, free amino acids and bioactive amines were determined. The physicochemical parameters were evaluated by official methods and analysis of amino acids and bioactive amines by ultra performance liquid chromatography (UPLC). Both cultivars showed linear increase in physical dimensions with time; Grappolo 541 had larger dimensions and higher increase rates; it was the best table olive. Moisture and phenolics contents decreased with time, whereas lipids increased for both cultivars. Ripened Arbequina had higher lipids contents which is desirable for olive oil. Free proline, arginine and tyrosine were found in the olives. Tyrosine was detected throughout development and correlated positively with phenolics. Arginine was detected in both cultivars when the fruit reached physiological maturity. Proline was detected only in Arbequina at physiological maturity. Among the ten amines investigated, only histamine, agmatine and phenylethylamine were detected, and histamine was the most prevalent. Agmatine was present only in Grappolo 541, and phenylethylamine in both cultivars but only in early stages of development. Histamine levels increased in Arbequina, but decreased in Grappolo 541 in early development stages. Agmatine was detected throughout development. Studies should be conduzed to further investigated the functions of this amines in the olive fruit.